Implementasi Digitalisasi Kurikulum Merdeka Di SD Negeri 3 Tenggeles Kudus Dengan Media Canva Sebagai Pengabdian Kuliah Kerja Nyata: (Implementation of the Digitalization of the Independent Curriculum at SDN 3 Tenggeles Kudus Using Canva Media as a Community Service Program) - Nasywa Ayu Malihah; Charisma Dwi Riyani; Lutfi Maelatun Z.H; Novita Amelia Rahmawati (Prodi Tadris IPA Biologi UIN Mataram, 2024)
One of the villages in Kudus Regency's Mejobo District, Tenggeles, is seeing an increase in its productive generation. Equipped with this insight, the team responsible for implementing the activity decided to promote the potential of the community in the field of education, particularly at SD Negeri 3 Tenggeles. Student empowerment at SD Negeri 3 Tenggeles will be carried out through the deployment of Independent Curriculum digitalization with Canva media. This program's primary goal is to raise awareness of the value of digital technology proficiency for future acquisition of other soft skills. The sixth graders at SD Negeri 3 Tenggeles are the program's target audience; they can be thought of as a high class that is prepared to advance to the next grade level by receiving further knowledge. Training and accompanying strategies are used in the implementation of this program. The procedure begins with the introduction of Canva and the material presentation. Next, the design team collaborates with the team implementing the activity, and finally, the work is presented in front of the class. As a result of this program's adoption, kids' creativity is being encouraged and their teamwork skills are improving.